Modeling of Solvent Effects in the Electrical Response of π-Stacked Molecular Junctions - Ghane, Tahereh; Kleshchonok, Andrii; Gutierrez, Rafael; Cuniberti, Gianaurelio (Giovanni) (Journal of Physical Chemistry C, 2015)
(Chemical Equation Presented) We present theoretical modeling of the influence of THF solvents on the mechanical stability and the electrical response of two different π-stacked molecular junctions based on cysteamine conjugates of naphthalic anhydride and of pyrene. Combining molecular dynamics simulations and quantum transport calculations, we show that for junctions with a weaker π-π stacking - as measured by the stacking energy - dynamical breaking of the stacking induced by the solvent can take place. However, contrary to what may be expected, the conductance of the system is not suppressed due to the emergence of an additional transport channel which bypasses the broken π overlap of the perylene cores. However, an additional gating-like effect in such a situation does reduce the low bias current when comparing with situations, where π-stacking is preserved.
CRIS-Team Scopus Importer:2023-03-20